Undestanding Vygotsky : a quest for synthesis - Van der Veer, René; Valsiner, Jaan (Oxford GB: Blackwell, 1993)
Trata acerca de la vida y obra de Lev Vygotsky.
Keywords: RUSIA; PSICOLOGIA; EDUCACION; PSICOPEDAGOGIA; BIOGRAFIAS; VYGOTSKY, LEV SEMENOVICH